The Effect of Some Immunological Markers (IgM, IgG, CCP, IL1) Associated with RA in a Sample of Iraqi Patients: Pengaruh Beberapa Penanda Imunologi (IgM, IgG, CCP, IL1) yang Berhubungan dengan RA pada Sampel Pasien Irak - Ahmed, Atheer Shehab; Al-Ezee, Ali Shakir; Sahm, Sara Fawzi (Universitas Muhammadiyah Sidoarjo, 2024)
This work was performed on Iraqi patients with rheumatoid arthritis. It collected blood samples from 60 patients with RA whose ages range between 21-70 years. The study included more females than males, as the former was 55 by 91.7%, while the latter was 5 at 8.3%. To compare, 28 other blood samples were drawn from healthy control participants who range from 21-60 years, and the males was 5, 17.9%. The females were 23 by 82.1%, as the highest was in the ages 41-60 years and 51.7 and the age group (≤20) years (3.3%) was lowest as the disease among non-smokers(90.0%) is the largest in comparison to the rate among smokers (10.0%) with significant differences (P<0.001). The disease among married couples (80.0%) was statistically different (P<0.01) as the largest in reference to the unmarried and (20.0%). A significant rise (P<0.001) in Intreleukin- 1 alpha in patients 2.87 units/ml appeared while in healthy people 1.36 units/ml, and a significant rise